Optimal path planning of logistics distribution of urban and rural agricultural products from the perspective of supply chain - Wang, Xiumei; Song, Xiaoli (Informatica, 2023)
Logistics distribution is a crucial part in the supply chain of agricultural products. This paper optimized the distribution path of agricultural products between distribution centers and customers using the adaptive genetic algorithm and conducted a simulation comparison with greedy and traditional genetic algorithms. The results showed that although the greedy algorithm obtained the path planning scheme faster, the planning path obtained by the genetic algorithm was better, and the adaptive genetic algorithm obtained a shorter distribution path, lower transportation cost, and less computation time than the traditional genetic algorithm.